Risk Management Practices and Financial Sustainability of Rotating Saving and Credit Associations in Kajiado County, Kenya. (Cuea Journal of Business and Economics, 2025)
Financial sustainability remains a critical concern across various sectors as organizations respond to economic volatility and the global demand for sustainable development. Rotating Savings and Credit Associations (ROSCAs) are informal financial associations that serve as crucial financial lifelines for underserved communities, especially in Kajiado County, Kenya. This study examined the influence of risk management practices on the financial sustainability of ROSCAs in Kajiado County, Kenya. This study explored the role of risk management practices in enhancing the long-term viability of ROSCAs. Grounded in the Risk Management Theory, the research employed a descriptive cross-sectional survey design and used a quantitative methodology. The target population was 80 active ROSCAs in Kajiado County, all of which were included in the census, and using structured questionnaires to collect the data. Descriptive statistics and multiple linear regression were used to analyze the data. The findings revealed a positive and statistically significant relationship between risk management practices and financial sustainability (β = 0.38, p < 0.001). The study recommended strengthening risk management frameworks, integrating mobile-based financial tools such as M-PESA, and institutionalizing regular audits to promote transparency, member confidence, and financial stability in Kenya’s informal financial ecosystem.